1999
DOI: 10.1007/s007010050355
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Somatosensory Pathways by Focal-Cooling-Induced Changes of Somatosensory Evoked Potentials and EEG-Activity - an Experimental Study

Abstract: Focal cooling of the cortex induces easily recognizable and reversible changes of the bio-electrical activity without causing any histological damage. Therefore the method seems suitable for identifying eloquent areas. It can be expected that clinical application of the cooling technique in combination with intraoperative electrophysiological monitoring will be helpful to further lower the risk of neurosurgical operations. We propose that cooling mainly interferes with the synaptic transmission within the soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Previous electrophysiological studies have revealed that temperature changes can also modulate neural activity (Bindman et al, 1963;Moseley et al, 1972;Moser et al, 1993;Sabatini and Regehr, 1996;Hupé et al, 1998;Schwerdtfeger et al, 1999;Aihara et al, 2001;Long and Fee, 2008;Stujenske et al, 2015;Ait Ouares et al, 2019;Owen et al, 2019). However, how this modulation occurs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous electrophysiological studies have revealed that temperature changes can also modulate neural activity (Bindman et al, 1963;Moseley et al, 1972;Moser et al, 1993;Sabatini and Regehr, 1996;Hupé et al, 1998;Schwerdtfeger et al, 1999;Aihara et al, 2001;Long and Fee, 2008;Stujenske et al, 2015;Ait Ouares et al, 2019;Owen et al, 2019). However, how this modulation occurs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that, during an epilepsy episode, cooling the brain could cease hyperactivity in human patients (Ommaya and Baldwin, 1963;Karkar et al, 2002;Nomura et al, 2014), as well as in animals (Motamedi et al, 2006;Inoue et al, 2017). Other studies have reported contradictory findings, i.e., that cooling the brain increases neural activity (or that heating the brain decreases neural activity; Bindman et al, 1963;Moser et al, 1993;Schwerdtfeger et al, 1999;Ait Ouares et al, 2019;Owen et al, 2019). More importantly, little is known about the effects of temperature on brain information processing at the network level, where multiple inputs of different neurotransmitters are integrated (e.g., glutamate, GABA, dopamine, et cetera).…”
Section: Introductionmentioning
confidence: 99%
“…16) Focal cooling of the somatosensory cortex in rats by 209 C for 5 minutes induces recognizable changes of the somatosensory evoked potential, which are fully reversible after warming up the tissue. 25) These studies suggest that reversible neurophysiological dysfunctions are induced at a threshold temperature of approximately 209 C.…”
Section: Influence Of Focal Cooling On Neurophysiological Functionsmentioning
confidence: 97%
“…Cooling has been shown to suppress reversibly normal central nervous system activity (4)(5)(6)(7)(8)(9)(10)(11)(12). Several in vitro and in vivo studies have demonstrated that focal brain cooling also reduces epileptiform activity in seizure models (13)(14)(15)(16)(17)(18) and in humans (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%